2022
DOI: 10.1021/acs.macromol.2c00317
|View full text |Cite
|
Sign up to set email alerts
|

Connection between Intrapore Free Energy, Molecule Permeation, and Selectivity of Nanofiltration Membranes

Abstract: Purification and separation by nanofiltration is a fascinating interdisciplinary topic that is being actively studied both in polymer science and nanoscience/nanotechnology. However, a comprehensive understanding of the separation mechanism based on a sound physical foundation for the nanofiltration process of aqueous solutions remains very challenging and not well established. To confront this issue, in this study we developed a physical model that is motivated by classic polymer physics for the permeation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 88 publications
0
1
0
Order By: Relevance
“…S11), indicating a nonlinear dependence of permeate flux on pressure. A recent theoretical study revealed that a chain of solvents must overcome a critical energy barrier before being able to permeate through the membrane pores ( 47 , 48 ), resulting in a nonlinear dependence of permeate flux on applied pressure (see derivation in the Supplementary Materials) ( 49 53 )J=k(PPc)exp(PcP)where J is the permeate flux, k is a proportionality factor, P is the applied pressure, and P c is the critical pressure. On the basis of Eq.…”
Section: Resultsmentioning
confidence: 99%
“…S11), indicating a nonlinear dependence of permeate flux on pressure. A recent theoretical study revealed that a chain of solvents must overcome a critical energy barrier before being able to permeate through the membrane pores ( 47 , 48 ), resulting in a nonlinear dependence of permeate flux on applied pressure (see derivation in the Supplementary Materials) ( 49 53 )J=k(PPc)exp(PcP)where J is the permeate flux, k is a proportionality factor, P is the applied pressure, and P c is the critical pressure. On the basis of Eq.…”
Section: Resultsmentioning
confidence: 99%